2009
DOI: 10.1016/j.jpor.2009.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Chewing-related prefrontal cortex activation while wearing partial denture prosthesis: Pilot study

Abstract: We concluded that a partial dental prosthesis significantly stimulates both masticatory muscle and dorsal prefrontal cortex activities, which might contribute to the prevention of cognitive impairment in aged individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 27 publications
3
50
0
Order By: Relevance
“…On the other hand, OD patients did not demonstrate any significant modifications of occlusal state or chewing activities as compared to HC subjects. It has been previously reported that prefrontal activity during chewing is involved in food preference [29], selfevaluation of chewing ability [35,40], food reward [35], food representation, and monitoring of eating behavior [52]. Furthermore, the DLPFC and m-PFC are also involved in multisensory sensory functioning as well as execution, attention, and working memory participations [25][26][27][28][29]32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, OD patients did not demonstrate any significant modifications of occlusal state or chewing activities as compared to HC subjects. It has been previously reported that prefrontal activity during chewing is involved in food preference [29], selfevaluation of chewing ability [35,40], food reward [35], food representation, and monitoring of eating behavior [52]. Furthermore, the DLPFC and m-PFC are also involved in multisensory sensory functioning as well as execution, attention, and working memory participations [25][26][27][28][29]32].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, prefrontal cortical activities were simultaneously recorded during chewing in order to further evaluate whether prefrontal activities during chewing were associated with somatization subscale scores obtained with the SCL-90-R [38,39]. We also determined occlusal status in terms of occlusal force and occlusal contact area using the Dental Prescale occlusal diagnostic system (Fujifilm Corp., Kuala Lumpur, Malaysia), because chewing-related prefrontal activity and occlusal discomfort during chewing are modulated not only by psychiatric state, but also by alterations of the oral environment, such as tooth loss [40], occlusal interference, and malocclusion [41]. The fNIRS measurements did not interfere with the EMG electrodes or jaw movement tracking while evaluating chewing performance in this study (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It was beneficial for cognitive impairment during the early intervention in that vascular risk factors could be found and easily controlled [6]. Dental prosthesis could significantly stimulate masticatory muscle and dorsal prefrontal cortex activities [9], and increase cerebral regional blood volume [10].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, an association between tooth number and cognitive status has been reported [11,13,14,[23][24][25][26]. Furthermore, a number of case-series suggest that restoration of tooth loss and masticatory function by adequate prosthesis can lead to an improvement in functional brain activity [17,20,27]. However, to our knowledge there is no solid evidence on the role of functional quality of denture in the cognitive status of edentate elders.…”
Section: Introductionmentioning
confidence: 99%